Optimization of Visual Puzzle Media Utilization to Enhance Geometry Understanding in Elementary Schools: An Analytical Study - Mifta Hasni, Zilma; Puspani, Uni; Nuraffiatul Jannah, Diah; Juhji, Juhji (Tarunateach: Journal of Elementary School, 2024)
This research aims to analyze literature that discusses using visual puzzle media to increase the understanding of geometry in method elementary schools. The research used is qualitative research with a literature review approach. The research steps include article collection, reduction, display, discussion, and conclusion. The data source comprises national journal articles published in the last ten years. The research results show that six of the ten articles reviewed are relevant to the research topic; visual puzzle media has proven effective in increasing students' understanding of geometry. It is proven by increased learning outcomes and student achievement in geometry material when visual puzzle media is applied.